2023
DOI: 10.1182/blood.2022018598
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of CD19 and CD22 with Bicistronic CAR-T cells in Patients with Relapsed/Refractory Large B Cell Lymphoma

Abstract: Relapse following CD19-directed chimeric antigen receptor T-cells (CAR-T) for relapsed/refractory large B-cell lymphoma (r/r LBCL) is commonly ascribed to antigen loss or CAR-T exhaustion. Multi-antigen targeting and PD-1 blockade are rational approaches to prevent relapse. Here, we test CD19/22 dual-targeting CAR-T (AUTO3) plus pembrolizumab in r/r LBCL as inpatient or outpatient therapy (NCT03289455, https://clinicaltrials.gov/ct2/show/NCT03289455). Endpoints include toxicity (primary) and response rates (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Consequently, a goal is to find strategies in which CAR T cells have the capacity to detect the antigen loss and switch their specificity or can detect multiple targets a priori. In multiple myeloma, dual CAR T‐cell targeting was tested by co‐infusion of two different CAR T‐cell constructs (dual CAR) or one CAR T‐cell construct targeting multiple molecules (tandem CAR) including BCMA and CD19, CD22, or GPRC5D 79–81 . Currently, a variety of combinations are being tested.…”
Section: Antigen Loss or Downregulationmentioning
confidence: 99%
“…Consequently, a goal is to find strategies in which CAR T cells have the capacity to detect the antigen loss and switch their specificity or can detect multiple targets a priori. In multiple myeloma, dual CAR T‐cell targeting was tested by co‐infusion of two different CAR T‐cell constructs (dual CAR) or one CAR T‐cell construct targeting multiple molecules (tandem CAR) including BCMA and CD19, CD22, or GPRC5D 79–81 . Currently, a variety of combinations are being tested.…”
Section: Antigen Loss or Downregulationmentioning
confidence: 99%
“…Analysis of the clinical outcome led to the development of a novel bicistronic CD19.28ζ/CD22.BBζ construct with enhanced cytokine production against CD22 in preclinical models 37 . Another strategy targeting CD19 and CD22 with bicistronic CAR T‐cells (AUTO3) was tested in patients with ALL 38 (AMELIA trial: NCT03289455) as well as in relapsed/refractory DLBCL 39 (ALEXANDER trial: NCT03287817) and convincing primary results have been reported. As the position of the two scFv domains has an influence on their functionality, these CAR T‐cells still require optimization 117 .…”
Section: Strategies For Controlling Car T‐cell Activitymentioning
confidence: 99%
“…CD22 with bicistronic CAR T-cells (AUTO3) was tested in patients with ALL38 (AMELIA trial: NCT03289455) as well as in relapsed/ refractory DLBCL39 (ALEXANDER trial: NCT03287817) and convincing primary results have been reported. As the position of the two scFv domains has an influence on their functionality, these CAR Tcells still require optimization 117.…”
mentioning
confidence: 99%
“…103 Current efforts to "diversify" CAR T-cell populations that are already in clinical testing include the development of bicistronic (expression of two separate receptors in the same cell) and tandem (two binders in the same receptor) CAR T cells with dual specificity. 104,105 Whether one strategy is superior to the other awaits more results from the trials.…”
Section: Synthetic Circuits That Diversify T-cell Populationsmentioning
confidence: 99%